Export Potential of Horticultural Products: Constraints and Strategies - K.H. Vedini (Journal of Agricultural Extension Management, 2025)
Horticultural sector has the highest potential for export, owing to the wide diversity of horticultural flora, agro-climatic conditions coupled with efficient low cost labour and advantageous geographic location. Indi a has an edge over other producing countries to expand its export basket and exploit the hitherto untapped potential indigenous germplasm. However, the above stated climatic diversity offer equally diverse problems in post harvest handling of produce due to their varying shapes, sizes she lf life , nature of ripening and varied storage, transport and packaging requirements. Marketing is an important step in the post harvest handling of the horticultural produce. It is the most complicated issue that requires better understanding of the complexities and identification of the bottlenecks to provide an efficient solution. An efficient and effective marketing system is a boon to any production system in agriculture and horticulture in particular